2014
DOI: 10.1557/mrc.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

Ion-modulated transistors on paper using phase-separated semiconductor/insulator blends

Abstract: We have used phase-separated poly(3-hexyltiophene) (P3HT)/poly(L-lactic acid) (PLLA) blends to fabricate low-voltage ion-modulated transistors on a rough paper substrate. The semiconductor and insulator are mixed together in a solution and spin casted onto the paper substrate. Owing to their different solubilities and surface energies the P3HT and PLLA will phase separate vertically during the spinning process creating a thin layer of semiconductor on top of the insulator. This thin semiconductor layer, diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…Owing to the large capacitance of the ion-gel electrolyte, these TFTs also had very low operating voltages (2 V), but a significantly improved on/off current ratio (about 10 6 ). On a 3-stage unipolar ring oscillator, the authors measured a signal propagation delay of 35 ms per stage at a supply voltage of 3 V. 22 In 2011, we showed that the large surface roughness of paper does not necessarily prevent the use of very thin gate dielectrics in the fabrication of organic TFTs. 24 Employing a hybrid gate dielectric consisting of a 3.6 nm-thick layer of oxygen-plasma-grown aluminum oxide (AlO x ) and a 2.1 nm-thick self-assembled monolayer (SAM) of an alkylphosphonic acid, we fabricated bottom-gate, top-contact p-channel and n-channel TFTs and unipolar and complementary inverters directly on the surface of four different types of banknotes.…”
Section: Organic Field-effect Transistors On Papermentioning
confidence: 94%
See 1 more Smart Citation
“…Owing to the large capacitance of the ion-gel electrolyte, these TFTs also had very low operating voltages (2 V), but a significantly improved on/off current ratio (about 10 6 ). On a 3-stage unipolar ring oscillator, the authors measured a signal propagation delay of 35 ms per stage at a supply voltage of 3 V. 22 In 2011, we showed that the large surface roughness of paper does not necessarily prevent the use of very thin gate dielectrics in the fabrication of organic TFTs. 24 Employing a hybrid gate dielectric consisting of a 3.6 nm-thick layer of oxygen-plasma-grown aluminum oxide (AlO x ) and a 2.1 nm-thick self-assembled monolayer (SAM) of an alkylphosphonic acid, we fabricated bottom-gate, top-contact p-channel and n-channel TFTs and unipolar and complementary inverters directly on the surface of four different types of banknotes.…”
Section: Organic Field-effect Transistors On Papermentioning
confidence: 94%
“…The hygroscopic nature of the PVP resulted in a very large gate-insulator capacitance, allowing these TFTs to be operated with voltages of about 1 V. However, due to the significant leakage currents, the TFTs in this initial report had a very small on/off current ratio (about 10). On the same type of paper, Pettersson et al 22 later fabricated P3HT TFTs in which an ion-gel electrolyte obtained by gelation of a triblock copolymer (poly(styrene-block-ethylene oxide-block-styrene); PS-PEO-PS) in an ionic liquid (1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; [EMIM][TFSI]) 23 was employed as the gate insulator. Owing to the large capacitance of the ion-gel electrolyte, these TFTs also had very low operating voltages (2 V), but a significantly improved on/off current ratio (about 10 6 ).…”
Section: Organic Field-effect Transistors On Papermentioning
confidence: 99%
“…The hysteresis observed in the drain current is as expected for ion‐modulated transistors; lower when measuring in the forward direction and higher in the backward direction. This is a result of the fact that these devices operate electrochemically with the used ICon . The process of reversibly doping and de‐doping the semiconductor during operation is slow due to the internal ICon resistance that hinders the motion of ions.…”
Section: Resultsmentioning
confidence: 99%
“…The transistor model used in this paper has been demonstrated in previous papers . The transistor is a p‐channel low‐voltage ion‐modulated device, utilizing a solidified sorbitol‐based ionic‐liquid as the electrolyte.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation